Low-molecular protectors in salicylate-deficient plants of Arabidopsis thaliana under influence of salt stress - Yastreb, T. O.; Kolupaev, Yu. E.; Obozniy, A. I.; Karpets, Yu. V.; Dmitriev, A.P. (Reports of the National Academy of Sciences of Ukraine, 2016)
The responses to the salt stress (200 mM NaCl, 24 h) of Arabidopsis thaliana plants of wild type (Col-0) and those transformed with the gene of bacterial salicylate hydroxylase (NahG), which have lower content of salicylic acid, have been compared. After the salt stress, the growth of wild type plants was considerably inhibited, while its effect on the growth of NahG transformants was weakly expressed. After the salt stress in the leaves of plants of both genotypes, the contents of chlorophyll and carotinoids were decreased; however, in NahG plants, the changes of the contents of photosynthetic pigments were less revealed than in wild type plants. In response to the NaCl stress, the increase of the proline content in leaves of wild type plants was more essential in comparison with that in salicylate-deficient transformants. At the same time, the contents of carbohydrates and anthocyanins in leaves of NahG plants in response to the salt stress were increased, and those in the wild-type plants were decreased. The conclusion is made about the distinctions in the contributions of low-molecular protective compounds in adaptation of Arabidopsis plants of the wild type and those transformed with the bacterial gene of salicylate hydroxylase to the salt stress.